2016
DOI: 10.1002/clen.201500966
|View full text |Cite
|
Sign up to set email alerts
|

Probabilistic Approach to Evaluation of Metal(loid) Fate During Stormwater Aquifer Storage and Recovery

Abstract: Research Article Probabilistic Approach to Evaluation of Metal(loid) Fate During Stormwater Aquifer Storage and RecoveryThe fate of metal(loid)s is a key consideration when recycling urban stormwater via the aquifer, due to their potential within urban stormwater from anthropogenic sources and also the potential for mobilization from the aquifer sediments. A probabilistic modeling approach incorporating the use of probability density functions was applied to assess the capacity of a confined, anoxic limestone … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 26 publications
1
11
0
Order By: Relevance
“…The iron concentrations from production wells (PW-Sand and PW-Gravel) were higher than those of the groundwater (GMW-Sand: 14.1 ± 1.1 mg/L and GMW-Gravel: 10.3 ± 0.9 mg/L). Previous studies reported the occurrence of high iron concentrations in MAR [22,23]. The amount of manganese in the river water was 0.2 mg/L, but it was higher in the RBF filtrate samples (PW-Sand (1.5 ± 0.1 mg/L) and PW-Gravel (2.6 ± 0.8 mg/L)).…”
Section: Iron and Manganesementioning
confidence: 82%
“…The iron concentrations from production wells (PW-Sand and PW-Gravel) were higher than those of the groundwater (GMW-Sand: 14.1 ± 1.1 mg/L and GMW-Gravel: 10.3 ± 0.9 mg/L). Previous studies reported the occurrence of high iron concentrations in MAR [22,23]. The amount of manganese in the river water was 0.2 mg/L, but it was higher in the RBF filtrate samples (PW-Sand (1.5 ± 0.1 mg/L) and PW-Gravel (2.6 ± 0.8 mg/L)).…”
Section: Iron and Manganesementioning
confidence: 82%
“…[3] below) in the T2 aquifer, which is consistent with the concentration of BDOC in the present study. Iron(III) in sediments of the storage zone has been reported to be an important oxidant for reaction with TOC, and therefore the removal of BDOC is unlikely to be limited by the availability of oxidants (Vanderzalm et al, 2016). …”
Section: Resultsmentioning
confidence: 99%
“…Four stormwater harvesting and aquifer storage and recovery schemes: Parafield, Kaurna Park, Unity Park, and Paddocks. The figure shows City of Salisbury stormwater harvesting facilities, identifying the location of managed aquifer recharge (MAR) wells at the associated catchments (Vanderzalm et al 2016). …”
Section: Methodsmentioning
confidence: 99%
“…As a result, the solubility and mobility of metalloids may fluctuate within an individual MAR operation [95]. Iron solubility is commonly modified by changing redox conditions in MAR [96]. Reductive iron (III) dissolution not only increases dissolved iron concentrations, but the reduction in sorption sites also leads to increases in other dissolved metalloid concentrations.…”
Section: Metal(loid) Fatementioning
confidence: 99%
“…The fate of metals and metalloids were investigated in four, large-scale, stormwater ASR systems in South Australia located in a confined, anoxic, limestone aquifer [96]. Variations in source water concentrations and aquifer conditions complicated the process of attempting to use deterministic methods to estimate environmental risk.…”
Section: Metal(loid) Fatementioning
confidence: 99%